2003
DOI: 10.1034/j.1600-0544.2003.245.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional assessment of treatment outcomes on the face

Abstract: It was concluded that in this preliminary study that whether treatment is undertaken with or without extractions, in this group of patients the facial morphology was not significantly different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…McCance et al [1] tried to analyze the soft tissue changes after surgery in three dimensions using a laser scan. Moss et al [2] suggested that the laser scan could be an effective tool to evaluate the three-dimensional (3D) changes after orthodontic treatment. However, the laser scan could not reveal the relations between the soft tissue and the underlying hard tissue.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…McCance et al [1] tried to analyze the soft tissue changes after surgery in three dimensions using a laser scan. Moss et al [2] suggested that the laser scan could be an effective tool to evaluate the three-dimensional (3D) changes after orthodontic treatment. However, the laser scan could not reveal the relations between the soft tissue and the underlying hard tissue.…”
Section: Purposementioning
confidence: 99%
“…Reliability engineering concerns the probability that a system will perform its intended function during a specified period of time under defined conditions [1,2]. Reliability, R(t) = P{T[t} is the probability that a component or device will perform its function for a specified period of time under stated operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There is no need of cast preparation as e-models are prepared from scanned impressions. Images have been created to establish databases for normative populations[71] and cross-sectional growth changes,[72] and also to assess the clinical outcomes in surgical[737475] and non-surgical treatments[7677] in the head and neck regions.…”
Section: Hard Tissue Applicationsmentioning
confidence: 99%
“…5 We have been considering the application of this technique in the assessment of rhinoplasty patients, and we plan to use the technique to document cosmetic change following simple septoplasty surgery. 1 -4 Recent software development has extended the use of such systems; they can now be used to accurately analyse surgery outcomes, as well as to enable surgical simulation of the probable changes following operative intervention.…”
Section: Introductionmentioning
confidence: 99%